2021
DOI: 10.3389/fonc.2021.644612
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Immunotherapeutic Value of CD248 in Renal Cell Carcinoma

Abstract: Background: Renal cell carcinoma (RCC) is the most common malignancy in the urinary system. Despite substantial improvements in available treatment options, the survival outcome of advanced RCC is unsatisfactory. Identifying novel biomarkers to assist in early diagnosis and to screen patients who are sensitive to immunotherapy would be beneficial. CD248 is a promising candidate that deserves to be investigated.Methods: The Cancer Genome Atlas (TCGA) data set and clinical specimens were adopted to analyze the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Pericytes provide structural support for endothelial cells and thus stabilize the vasculature. In our previous study, we found that CD248 was expressed specifically in HCC and RCC, and overexpression of CD248 was related to a poor prognosis ( 31 , 32 ). Davies et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pericytes provide structural support for endothelial cells and thus stabilize the vasculature. In our previous study, we found that CD248 was expressed specifically in HCC and RCC, and overexpression of CD248 was related to a poor prognosis ( 31 , 32 ). Davies et al.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study, we found that PSMA and CD248 were both expressed specifically in the vasculature in hepatocellular carcinoma (HCC), and vascular-expressed PSMA and CD248 might be used as prognostic markers and vascular therapeutic targets for HCC (30,31). We also found that overexpression of CD248 in renal cell carcinoma (RCC) was related to poor prognosis (32). Therefore, we wondered whether vascular-expressed PSMA and CD248 could be promising biomarkers for UCB.…”
Section: Introductionmentioning
confidence: 99%
“…In short, a CD248-based prognostic signature has an excellent ability to predict the prognosis of patients with AUC =0.889 (16). Therefore, CD248 might bridge the gap between angiogenesis and immunosuppression, and thus be a promising prognostic and therapeutic target for RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the overexpression of CD248 could reflect an immunosuppressive TME and is inversely correlated with the prognosis of patients with RCC (16). In this paper, we further analyzed the gene expression profiles and clinical information of RCC patients both from The Cancer Genome Atlas (TCGA) and clinical records.…”
Section: Introductionmentioning
confidence: 99%
“…Pericytes provide structural support for endothelial cells and thus stabilize the vasculature. In our previous study, we found that CD248 was expressed specifically in HCC and RCC, and overexpression of CD248 was related to a poor prognosis (31,32). Davies et al (51) reported that overexpression of CD248 correlated negatively with the clinical outcome of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 91%